Theoretical analysis of cold-formed stainless steel tubular joints. (15th January 2015) - Feng, Ran; Young, Ben
Highlights: Cold-formed stainless steel tubular T- and X-joints have been investigated. The effect of axial chord preload on the joint strength has been taken into consideration. Design rules of cold-formed stainless steel tubular joints are proposed. The proposed equations were derived through a combination of theoretical and empirical analyses. Abstract: A theoretical investigation on cold-formed stainless steel tubular T- and X-joints fabricated from square and rectangular hollow section (SHS and RHS) brace and chord members was conducted in this study to develop analytical models. High strength stainless steel (duplex and high strength austenitic) and normal strength stainless steel (AISI 304) specimens were considered in the study. The yield line mechanism analysis which is based on the deformed shape of the axially loaded tubular joints observed from experimental and numerical investigations was performed to estimate the stainless steel tubular joint strengths subjected to chord face failure. The yield line models considered the weld size, the rounded corners of the chord member and the plastic hinges at the chord webs. In addition, the membrane force in the chord flange and the strain hardening of the material were also considered in the models. The effect of axial chord preload on the joint strength has been taken into account for the X-joints. Some existing theoretical models were also used to predict the structural behaviour of cold-formed stainless steel tubular joints subjected to chord side wall failure. The design rules for cold-formed stainless steel tubular joints failed by chord face and chord side wall were derived through a combination of theoretical and empirical analyses. Good agreements were achieved between the joint strengths predicted by the proposed design formulae and the results obtained from the experimental and numerical investigations.